The Influence of Job Level and Work Stress on Learning Motivation of Master's Students at Harapan Bangsa Business School Class of 2023-2024 - Damianus Tulus Rahmat; Mentiana Sibarani (Journal of World Science, 2024)
The demands of balancing professional and academic responsibilities present unique challenges for Master’s students who work while pursuing higher education, often resulting in increased job stress and varied impacts on learning motivation. This study investigates how job level and job stress influence the learning motivation of Master's students in Management at Harapan Bangsa Business School, focusing on students from the 2023-2024 cohort. A quantitative approach was used, employing structured questionnaires to collect data from a sample of 120 students in Bandung between July and November 2024. The analysis, conducted through multiple regression, revealed that job level significantly positively affects learning motivation, with students in higher positions exhibiting greater motivation to succeed academically. In contrast, job stress did not show a statistically significant effect on learning motivation, indicating that its impact may vary based on individual resilience and role-specific factors. These results suggest that learning motivation is more closely tied to job level than job stress. The study provides valuable insights for educational institutions aiming to enhance motivation among working students by promoting autonomy and competency support, aligning with Deci and Ryan’s self-determination theory. Institutions can better support students' academic success across different job levels by focusing on strategies that increase student autonomy and skill-building opportunities.